Tutorial Video Multimedia Development Learning of White Garden - Marlina, Marlina; Tresna, P.; Karmila, M. (INVOTEC, 2019)
The purpose of this study was to conduct a preliminary study of the learning media used, design and create multimedia video tutorials, perform validations from multimedia experts, material experts and users, revise, process data and analyze the results of multimedia validation of white embroidery tutorial videos. The research method used is the research and development method, this research phase starts from the design stage, the production and development stages, the validation stage and the revision stage. The findings were validated by a team of media experts, a team of material experts and users, that the embroidery tutorial multimedia videos were white and there were several revisions, namely the addition of information in the form of text in the video to the process of making white embroidery to avoid saturation. After revision, the media expert team validation results were 90.28%, the material expert team was 97.26% and 94.17% users. The conclusion is that the making of needy white embroidery tutorial multimedia is used in the learning process because it has a clear knowledge content, has an attractive and easily understood content and can be used in the white embroidery learning process.